Habilidades, roles y responsabilidades del docente de ciencias de la educación : hacia la tutoría en línea - Baquero Herrera, Sandra Julieth (Universidad de La Salle. Facultad de Ciencias de la Educación. Licenciatura en Lengua Castellana, Inglés y Francés (Lenguas Modernas)., 2017)
By the educational contexts evolve, the teacher's role is changed and the skills and strategies used in each educational setting; This transition presents a series of drawbacks that become challenges forcing him out of his comfort zone. La Universidad de la Salle, with publication of the booklet "Pedagogical use of ICT" (2012) planted its objectives and achievements for the incorporation of the pedagogical use of ICT in teaching practice. These objectives involve the preparation of teachers to assume the challenge of training mediated by information and communications technology. According with the last, the task of determining:. skills, roles and responsibilities of teachers of Science Education with the prospect of being tutor offline search results a objetc of investigation relevant completely to La Universidad de la Salle. This research explores that topic from reviewing various scenarios that enclose and bind the university educational agents with documents and district and national policies, as completion of a series of indicators intended to be as an instrument to identify and evaluate the characteristics of language teacher eventually, which intends to recognize and qualify their teaching to digital mediation; to be a virtual tutor of quality. That is, it aims to determine the skills, roles and responsibilities of teachers of science education with the focus of virtual tutor through a descriptive research linking bibliographic and documentary exploration, the analysis of works degree approach in technologies, iInformation and communication at the Education Faculty and the perception of students and teachers in the use of technologies in education, this allows to present and to define what skills, roles and responsibilities shall have teaching of spanish, english and french to serve as virtual tutor.